Modern Development of China's Cultural Industry - Huang, Yonglin. author. aut Link
XVI, 299 p. 30 illus.
Keywords: This book primarily investigates the historical development, fundamental theories, and resource utilization of China’s cultural industry, as well as the role of technological innovation in promoting the cultural industry’s growth. It specifically covers the historical choices and experiences of cultural industry development strategies since China’s reform and opening up, the achievements and future strategies of policies on cultural industry since the 18th National Congress, the core elements of cultural industry development and their relationships, characteristics of cultural consumption and its guidance, the integration of culture and tourism, the relationship between folk cultural resources and cultural industry development, etc. The book systematically studies the development of modern technological innovation in the cultural industry and its significant impact on contemporary cultural industry development, providing an in-depth analysis of the positive role that technological innovation plays in advancing the cultural industry. The research presented in this book elucidates the historical context, experiences, and issues of modern cultural industry development in China, expounds the fundamental relationships between cultural resources, technological innovation, and cultural industry development, and provides theoretical support and practical guidance for promoting the high-quality development of China's cultural industry.